Hubungan daya ledak otot tungkai terhadap smash open spike klub bola voli penjas universitas dehasen bengkulu - Syukur, Muhammad Abdul (Educative Sportive, 2020)
The purpose of this study is to determine the correlation between the explosive power of the leg muscles against the Smash Open Spike of the Physical Education club, Dehasen University of Bengkulu. The method used in this research is a correlational quantitative method. The population in this study were 12 athletes, the JPS volleyball club, Dehasen University, while the sample in this study were 12 athletes, namely all of them. The instruments in this study were a vertical jump test and a Smash Open Spike test. The data analysis requirements used were normality test with lilliefors and homogeneity test. The data analysis used was the product moment correlation analysis with a significance level of 5%. Based on the results of the study, it was found that there was a signifi.cant correlation between vertical jump (X) and the Smash Open Spike indicated by rx.y = 0.80> r (0.5) (12) = 0.632.